The Analysis of Spatial and Temporal Distribution of Daily Precipitation on the Central and South Western Iran - Amirhossein Halabian; Freshta Hosseinalipour; Fatemeh Jafari Shendi (جغرافیا و پایداری محیط)
In this research, temporal and spatial behavior of precipitation on the central and south western areas of Iran was studied at 114 synoptic, climatology and rain gauge stations, which had a statistic more than 10 years, in a period from 1329/10/11 to 1383/10/11. At first a 19724×114 matrix was obtained. Then, for each day in solar calendar, the mean daily precipitation calculated. In order to calculate precipitation for the area under study, digital maps with a spatial resolution of 14×14 Km daily maps have been calculated using Kriging method and, consequently, a new 366×3720 matrix was obtained. After that, an agglomerative hierarchical cluster analysis has been carried out on this matrix. The results of cluster analysis on Euclidean distance of this matrix based on Ward linkage method showed that according to the amount and time of received precipitation, four different precipitation regions were detected in the study area. These regions include super rainy, semi super rainy, super weak, and weak regions.